(untitled) (Transport systems and technologies, 2019)
Transport activity creates significant ecological danger for the vital and technological activity of population and the environment. The scale of pollution is influenced by the flow of traffic in places of traffic congestion on traffic lights and congestion on highways. Analysis of the peculiarities of Ukrainian urban transport systems revealed the main problems associated with a significant increase in passenger and freight traffic volumes in modern cities. The transport system of the city is a constant source of hazardous chemical pollution of the air, reservoirs, agricultural zones, noise and vibration, which affects the health of the population and the state of the environment. The main environmental dangers of urban transport systems are the use of land, the emission of pollutants into the air from mobile sources, the formation and placement of waste of various classes of danger, the use of plant resources, acoustic effects, electromagnetic radiation and the formation of dust in the surface air layer. It is determined that the following environmental factors create the greatest environmental dangers: emissions of pollutants into the atmosphere. The environmental analysis of the Kyiv transport system has confirmed the general trend in Ukraine. It has revealed that the main toxic substance that contaminates air during the operation of road transport is Carbon (II) oxide.The study of individual public transport routes has revealed a high level of emissions of harmful substances to the environment. The analysis of the results allowed us to develop measures to reduce the level of environmental dangers of the city. To manage the transport network, solutions are to be made to improve the environment. The decision minimizes the negative environmental consequences, prevents ecologically determined diseases of the population and creates a comfortable environment for the citizens of Kyiv and guests of the city.